2012
DOI: 10.1017/s0033291712000827
|View full text |Cite
|
Sign up to set email alerts
|

The expression of positive and negative schizotypy in daily life: an experience sampling study

Abstract: The results support the construct validity of a multidimensional model of schizotypy and the ecological validity of the positive and negative schizotypy dimensions. ESM appears to be a promising method for examining the daily life experiences of schizotypic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
119
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 50 publications
21
119
2
Order By: Relevance
“…While, in the current sample, negative schizotypy was indicative of low levels of wellbeing, replicating previous research (Barrantes -Vidal, et al, 2013;Kwapil et al, 2012), this was not the case for positive schizotypy. Positive schizotypy, in the current sample of artists, did not have the same correlates as found in previous ESM research with undergraduate students (Barrantes-Vidal, et al, 2013;Kwapil et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…While, in the current sample, negative schizotypy was indicative of low levels of wellbeing, replicating previous research (Barrantes -Vidal, et al, 2013;Kwapil et al, 2012), this was not the case for positive schizotypy. Positive schizotypy, in the current sample of artists, did not have the same correlates as found in previous ESM research with undergraduate students (Barrantes-Vidal, et al, 2013;Kwapil et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…As found in previous research, negative schizotypy was associated with reduced positive affect, high levels of tension and low levels of excitement (Barrantes-Vidal, et al, 2013;Kwapil et al, 2012). These competing and different correlates with state and affective variables helps to inform previous research suggesting that positive symptoms predict creativity while negative symptoms do not, or even appear to inhibit creativity (Acar & Sen, 2012).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The nonclinical psychosis phenotype (i.e., psychosis-proneness) is observed and reliably measured at the level of schizotypic personality features (using trait-like measures) and psychotic-like experiences (using symptom-based measures; Kwapil et al, 1999, Stefanis et al, 2002and BarrantesVidal et al, 2010. A substantial body of work has demonstrated that psychometrically assessed schizotypy is associated cross-sectionally with laboratory, interview, cognitive, and biobehavioral measures of schizophrenic symptoms and impairment (Claridge, 1997;Raine, 2006;Blanchard et al, 2011;Kwapil et al, 2012). Furthermore, longitudinal research indicates that psychometric schizotypy is associated with the development of psychosis and schizophreniaspectrum disorders (e.g., Chapman et al, 1994;Gooding et al, 2005) with effect sizes as large as or larger than in studies of consanguinity.…”
Section: Introductionmentioning
confidence: 99%
“…This approach offers several advantages compared to traditional assessment procedures, including enhanced ecological validity, minimization of retrospective bias, and the possibility of assessing the context of experiences [28][29][30]. Notably, ESM has been shown to be a useful tool for examining the clinical and subclinical expressions of the schizophrenia spectrum (e.g., [31][32][33][34][35]) and, given that it captures the phenomenology of symptoms as they unfold in the real world, it may complement current efforts to clarify links between adversity subtypes and psychosis symptom domains.…”
Section: Introductionmentioning
confidence: 99%